Child Friendly School Learning Ecosystem with a Humanist Religious Approach Through Futuristic Learning at Islamic Elementary School - Mohammad Jailani; Dian Artha Kusumaningtyas; Zaki Abouelnasr Elbaghdadi (Universitas Islam Negeri (UIN) Salatiga, 2025)
Background & objectives: The implementation of a child friendly school ecosystem through religious habits and a humanist approach highlights the need for research on effective governance to create a safe, comfortable, and character building school environment. This study aims to evaluate the suitability of the learning ecosystem with humanist religious principles, identify strengths and weaknesses, and provide strategic recommendations to improve adaptive and relevant learning. Method: Using a qualitative method with a case study approach, this research was conducted at SD Muhammadiyah Kleco Yogyakarta. The research followed four main procedures: 1) preparation, including problem identification and instrument design; 2) implementation, involving data collection through observation, interviews, and documentation; 3) analysis, where data was systematically processed and interpreted; and 4) reporting of findings. Informants, including teachers, students, and school principals, were selected through purposive sampling based on their relevance to the research objectives. Data collection involved observation, interviews, and documentation, followed by descriptive analysis through data reduction, data presentation, and conclusion drawing. Results: The study found that SD Muhammadiyah Kleco, Yogyakarta, implements child friendly schools through a noncoercive approach, strengthening Islamic character, and teacher-student-parent collaboration. The religious humanist approach emphasizes respectful interactions and moral education. Contribution of theory: Futuristic learning integrates technology but faces challenges in consistency and infrastructure. Supporting Al-Attas' Islamic Education Theory. Recommendations: This study recommends further research on technological adaptation and child friendly school policies in Islamic education.